Getting Paid to Hedge: Why Don’t Investors Pay a Premium to Hedge Downturns? - Kapadia, Nishad; Ostdiek, Barbara Bennett; Weston, James P.; Zekhnini, Morad (Journal of Financial and Quantitative Analysis, 2019)
Stocks that hedge sustained market downturns should have low expected returns, but they do not. We use ex ante firm characteristics and covariances to construct a tradable safe minus risky (SMR) portfolio that hedges market downturns out of sample. Although downturns (peaks to troughs in market index levels at the business-cycle frequency) predict significant declines in gross domestic product growth, SMR has significant positive average returns and 4-factor alphas (both around 0.8% per month). Risk-based models do not explain SMR’s returns, but mispricing does. Risky stocks are overpriced when sentiment is high, resulting in subsequent returns of -0.9% per month.